Buoyancy materials of aluminium borosilicate glass for high temperature resistance. (May 2015) - Zheng, B.; Zhuang, M. M.; Guo, A. R.; Wang, M. C.; Ren, S. E.; Geng, H. T.; Liu, J. C.
<x content-type="archive" xml:space="preserve">Abstract</x> Buoyancy materials with relatively high strength and temperature resistant were successfully fabricated. Because both the hollow microspheres and glass powders belong to borosilicate, the interfacial bond strength of the composites was very high. With the increase of sintering temperature before 750°C, the strength and density of the samples increased, which can be up to 15·8 MPa and 0·86 g cm–3, respectively. Besides, the thermal conductivity and water absorption can be kept at 0·15 W/(m K) and 3%, respectively. The authors chose aluminium borosilicate glass to replace the organic binders, which made the buoyancy materials withstand high temperature of 750°C while the traditional buoyancy materials decomposed above 300°C.